SIGNATURE VISUALIZATION METHOD - Malikova Ф.Ө; Toleushova А.Т; Ryskeldi Р.С (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In the modern information society, much attention is paid to improving the human and machine interface, which should ensure efficient processing of data and knowledge in simple, fast and accessible ways. One way to organize it is to introduce the manuscript (text input, drawings, drawings, etc.) its use usually does not require special training in a fast, convenient way. In addition, an integral part of the human-machine interface is mathematical and software, which allows you to move from the initial low data to data that directly characterizes the entered information. Currently, modern approaches to modeling the process of creating a handwritten text are considered. When examining the signature, an example of using the model is provided. The proposed visualization technique can be fully used on modern threedimensional monitors. Currently, the work on the computer analysis of the handwritten text is being actively carried out. In this case, from the handwritten text is extracted as transmitted with the help of information (recognition of the handwritten text), and information about the identity of the writer and his condition (identification of the person by handwriting and signature, psychological and medical diagnostics, graphological research).